Pengharapan Kristiani menurut Paus Fransiskus dan Relevansinya bagi Gereja pada Tahun Yubileum 2025 - Antonius P Sipahutar; Anasitasia Laia; Alexius Poto Obe (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Hope is one of the theological virtues strongly emphasized by Pope Francis, especially in the context of a world marked by suffering, crisis, and uncertainty. This article aims to present the Christian theological understanding of hope according to Pope Francis and to explore its relevance for the Church as it prepares for the Jubilee Year 2025. This study employs a documentary and textual theological analysis of Pope Francis’ catecheses, Sacred Scripture, official Church teachings, and the Jubilee documents. The findings show that Christian hope is rooted in the experience of God who accompanies, liberates, and consoles His people, and is grounded in the Paschal Mystery and the resurrection of Christ. Pope Francis deepens this vision through the figures of Sacred Scripture and through existential dynamics such as learning to hope, resisting despair, and remaining vigilant. Hope is both personal and ecclesial, as the Church is called to be a missionary of hope for the world. These insights highlight the importance of ongoing formation in the faith and concrete works of mercy as expressions of hope, especially as the Church enters the Jubilee Year 2025 as Pilgrims of Hope.